Numerical investigation of leakage in resonant exchange qubit - Lee, Tuck Chong (2018)
In this final year project, we study the effects of 1/f^α noise and nuclear field on leakage in a resonant exchange (RX) qubit. A 1/f^α noise sequence is generated via finite impulse response (FIR) method, and is then introduced into the RX qubit through a simple noise-induced model. In addition, we propose a simple model for degree of polarization (DOP) to characterize the nuclear field in terms of longitudinal and transversal direction. This thesis cross-examines various parameters related to 1/f^α noise and nuclear field, which include the exponent α, the strength of noise η, the standard deviation of nuclear spin distribution σ and DOP. The simulation demonstrates that leakage is predominantly due to the coupling between the logical qubit states and leakage states via different nuclear field components, and 1/f^α noise does not have significant leakage contribution.